IMPACT OF MANAGEMENT CONTROL SYSTEM ON THE QUALITY OF TEACHING IN NIGERIAN PUBLIC UNIVERSITIES - Abdulfatai Olanrewaju Nurudeen; Abdul Garba (Malete Journal of Accounting and Finance)
Quality of teaching of a given institute of learning can be linked to effective use of management control techniques by the management. Given the persistent report of poor quality of teaching in Nigerian Public Universities, despite the existence of management control system, this study examined the effects of management control system on the quality of teaching of federal universities in south western Nigeria The study adopts a mixed method research design (Quantitative and Qualitative). Questionnaire was used to obtain data from 231 respondents that are selected through multistage sampling technique for quantitative while 5 respondents purposively selected for qualitative data. Data were analysed using PLS-SEM while the Qualitative data also analysed thematically with NVIVO. Result control has positive effect on the universities performance with P-value 0.000, and β = 0.737 on teaching performance. Action control is significantly related to universities performance with P-value 0,001 and β= 0.593 for teaching performance. Personnel control (β = 0.011; t = 0.247; p > 0.05), also, found positively and significantly affect the quality of teaching in south-western public universities, Nigeria. The study therefore concluded that management control system is an essential tool for performance attainment through the teaching quality in Nigeria public universities. The study recommended that the universities should intensify efforts on effectiveness of the management control system, while the government should increase the funding and appraise the regulations in attempt improve the performance